Integration of Reflection and Self-Regulation as Factors of Personality’s Self-Actualization - Yuliia Kotelianets, Tetiana Dovha, Natalka Kotelianets, Tetiana Plachynda, (Opción, 2019)
The study aimed to determine the formation level of future professionals’ reflexive abilities and the development of a steady need for self-regulation of their activities via comparative quantitative research methods. As a result, the number of subjects with high and medium level of development of the reflexive component increased by 17.9% and 5.9%. In conclusion, the integration of reflection and self-regulation has a positive impact on the process of self-creation of the personality of a future professional